PRODUC – INITIATION SPORTS: A WAY TO ADDRESS VIOLENCE? (Fiep Bulletin - online, 2013)
This study refers to the project called PRODUC - Initiation Sport, held in the city of Duque de Caxias, in the state of Rio de Janeiro, in order to encourage sports in children and adolescents in the municipality. The aim of the study was a description of the Project related theories and violence that sustain it. The methodology was qualitative using a case study. The results were the presence of significant strengths and weaknesses. These denote that when correlated design theories design appears inadequate without foundation necessary to achieve the objective of improving the quality of lives of the target audience, and questioned the project is faced with the constituent elements of a project to seek funding from the ministries of Sport, 6 hits and 4 strong weak. Therefore, we conclude the absence of theoretical foundation, something essential in contributing to social problems of violence in the city, through education, culture and sports leisure.
Keywords: Physical Education; PRODUC - Initiation Sports; Violence.